2022
DOI: 10.1039/d2se00974a
|View full text |Cite
|
Sign up to set email alerts
|

Combination effect of flow channel configuration and anode GDL porosity on mass transfer and performance of PEM water electrolyzers

Abstract: Proton exchange membrane (PEM) water electrolyzer is being recognized as promising hydrogen production technology. Enhanced mass transfer of water can effectively ensure sufficient reactant supply, to achieve efficient hydrogen production....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…48 (2) Suitable pore distribution and porosity, which are essential for regulating the contact between the catalyst layer and the GDL to achieve efficient mass transfer between gas and liquid. 43,[49][50][51][52] (3) Excellent electrical and thermal conductivity to accelerate reaction kinetics as well as discharge the heat generated by the reaction in time, 53 (4) high corrosion resistance mitigates the negative impact of the operating environment and prolongs the cell lifespan. During the working process of the electrolytic cell, GDL often serves in a harsh, corrosive environment due to the high overpotential and oxygen-coupled acid generation in the anode.…”
Section: Gas Diffusion Layermentioning
confidence: 99%
“…48 (2) Suitable pore distribution and porosity, which are essential for regulating the contact between the catalyst layer and the GDL to achieve efficient mass transfer between gas and liquid. 43,[49][50][51][52] (3) Excellent electrical and thermal conductivity to accelerate reaction kinetics as well as discharge the heat generated by the reaction in time, 53 (4) high corrosion resistance mitigates the negative impact of the operating environment and prolongs the cell lifespan. During the working process of the electrolytic cell, GDL often serves in a harsh, corrosive environment due to the high overpotential and oxygen-coupled acid generation in the anode.…”
Section: Gas Diffusion Layermentioning
confidence: 99%
“…139 In general, increasing the porosity of GDLs is beneficial for the diffusion of the reaction gas; however, the conductivity of the electrode will decrease. 140 Although reducing porosity can enhance the conductivity of the electrode, it also hinders the transmission of gas. 141 In addition, the porosity distribution also seriously affects the uniform distribution of reaction gas and current density within the catalytic layer.…”
Section: Gas Diffusion Layers (Gdls) In Pemfcs With High Specific Pow...mentioning
confidence: 99%
“…Moreover, water generated from the reaction in PEMFCs needs adequate routes to be drained without flooding the CL and GDL [24][25][26]. Zhou et al [27] found that the ability of mass transfer was enhanced by reducing the length of the channel for gas flow and increasing the porosity of the anode GDL (A-GDL). Sim et al [28] reported a new approach to increasing the porosity and pore size of GDL by changing the gasket thickness, resulting in a positive effect on the drainage capacity.…”
Section: General Requirements For Gdlmentioning
confidence: 99%